Investigation of solidification behaviour of Mg–6Al and Mg–9Al alloys using in situ neutron diffraction. (January 2015) - Elsayed, A.; Sediako, D.; Ravindran, C.
<x content-type="archive" xml:space="preserve">Abstract</x> In situ neutron diffraction was used to examine the solidification behaviour of Mg–6 wt-%Al and Mg–9 wt-%Al alloys. Samples of each Mg–Al alloy were heated above their liquidus temperatures and stepwise cooled to 420°C while simultaneously collecting neutron scattering intensities. The solidified alloys were examined using scanning electron microscopy. Mainly blocky Mg17Al12 was found in Mg–6 wt-%Al alloy while branched Mg17Al12 adjacent to a large network of fine lamellar Mg17Al12 was found in the Mg–9 wt-%Al alloy. The neutron diffraction data accurately described the fraction solid growth as represented by the (<inline-graphic xlink:href="ark:/27927/pgh2gcv8k2t" xmlns:xlink="http://www.w3.org/1999/xlink" />) crystallographic plane over the entire solidification regime. The fraction solid of the Mg–6 wt-%Al alloy rose quickly at temperatures just below the liquidus point and rapidly approached 100% until solidification was complete while the Mg–9 wt-%Al alloy showed a more linear transition from liquid to solid. Neutron diffraction was also capable of detecting the formation of eutectic Mg17Al12 in the Mg–9 wt-%Al alloy. This research demonstrates unique possibilities in using neutron diffraction for further understanding of nucleation, eutectic formation and solid phase evolution of Mg alloys. On a utilisé la diffraction des neutrons in situ afin d'examiner le comportement de solidification des alliages Mg–6%Al en poids et Mg–9%Al en poids. On a chauffé des échantillons de chaque alliage d'Al–Mg au-dessus de leur température de liquidus et on les a refroidis en étapes jusqu'à 420°C tout en recueillant simultanément les intensités de diffusion des neutrons. On a examiné les alliages solidifiés en utilisant la microscopie électronique à balayage. Dans l'alliage Mg–6%Al, on a trouvé principalement du Mg17Al12 en blocs alors qu'on a trouvé du Mg17Al12 ramifié adjacent à un grand réseau de Mg17Al12 à lamelles fines dans l'alliage Mg–9%Al. Les données de diffraction des neutrons décrivaient avec précision la croissance de la fraction solide telle que représentée par le plan cristallographique (<inline-graphic xlink:href="ark:/27927/pgh2gcv8rkp" xmlns:xlink="http://www.w3.org/1999/xlink" />) du régime entier de solidification. La fraction solide de l'alliage Mg–6%Al s'élevait rapidement à des températures immédiatement au-dessous du point de liquidus et approchait rapidement 100% jusqu'à ce que la solidification soit complète alors que l'alliage Mg–9%Al montrait une transition plus linéaire de liquide à solide. La diffraction des neutrons était également capable de détecter la formation de l'eutectique Mg17Al12 dans l'alliage Mg–9%Al. Cette recherche démontre les possibilités uniques d'utilisation de la diffraction des neutrons pour comprendre davantage la nucléation, la formation d'eutectique et l'évolution de la phase solide des alliages de Mg.